Cell Penetrable Humanized-VH/VHH That Inhibit RNA Dependent RNA Polymerase (NS5B) of HCV - Thueng-in, Kanyarat; Thanongsaksrikul, Jeeraphong; Srimanote, Potjanee; Bangphoomi, Kunan; Poungpair, Ornnuthchar; Maneewatch, Santi; Choowongkomon, Kiattawee; Chaicumpa, Wanpen (PLOS ONE, 2012)
NS5B is pivotal RNA dependent RNA polymerase (RdRp) of HCV and NS5B function interfering halts the virus infective cycle. This work aimed to produce cell penetrable humanized single domain antibodies (SdAb; VH/VHH) that interfere with the RdRp activity. Recombinant NS5BΔ55 of genotype 3a HCV with de novo RNA synthetic activity was produced and used in phage biopanning for selecting phage clones that displayed NS5BΔ55 bound VH/VHH from a humanized-camel VH/VHH display library. VH/VHH from E. coli transfected with four selected phage clones inhibited RdRp activity when tested by ELISA inhibition using 3′di-cytidylate 25 nucleotide directed in vitro RNA synthesis. Deduced amino acid sequences of two clones showed VHH hallmark and were designated VHH6 and VHH24; other clones were conventional VH, designated VH9 and VH13. All VH/VHH were linked molecularly to a cell penetrating peptide, penetratin. The cell penetrable VH9, VH13, VHH6 and VHH24 added to culture of Huh7 cells transfected with JHF-1 RNA of genotype 2a HCV reduced the amounts of RNA intracellularly and in culture medium implying that they inhibited the virus replication. VH/VHH mimotopes matched with residues scattered on the polymerase fingers, palm and thumb which were likely juxtaposed to form conformational epitopes. Molecular docking revealed that the antibodies covered the RdRp catalytic groove. The transbodies await further studies for in vivo role in inhibiting HCV replication.